Assessing and Benchmarking reference EFL curricula in the Arab World in 2020 - Hiba Chendeb (European Scientific Journal, ESJ, 2020)
This research paper examines the efficiency of EFL curricula in the Arab world through assessing the status of EFL programs in terms of their appropriateness, applicability, and alignment to international curriculum standards. The study follows a mixed-method design where both qualitative and quantitative data are collected to gain insights into the EFL curricula designed in Lebanon, Syria, Jordan, Egypt, Saudi Arabia, Morocco, and Iraq before 2020. The findings of the survey questionnaire revealed that most of the 257 participants including teachers and coordinators had negative perceptions towards the curricula and considered that their drawbacks constituted a hurdle for reaching a high language proficiency level. The researcher conducted semi structured interviews with 20 teachers and coordinators who suggested restructuring and benchmarking curricula on a regular basis. Based on the results of the study, several aspects of EFL programs should be addressed to ensure an operative, efficacious, and practical implementation of curricula.